2015
DOI: 10.1016/j.soilbio.2015.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Root exudate carbon mitigates nitrogen loss in a semi-arid soil

Abstract: C mineralisation Immobilisation N:I index 15 N isotopic pool dilution Nitrification Nitrous oxide a b s t r a c tThe need for increased food production to support the growing global population requires more efficient nutrient management and prevention of nitrogen (N) losses from both applied fertiliser and organic matter (OM) decomposition. This is particularly important in semi-arid rainfed cropping soils, where soil water and temperature are the dominant drivers of N cycling rather than agricultural manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 72 publications
3
42
0
Order By: Relevance
“…Previous field and laboratory studies have reported such relationships under similar environmental conditions (Huang et al 2004;Gomes et al 2009). The fact that this relationship emerged despite environmental variation further highlights the importance of C abundance in regulating N 2 O emissions and supports the idea that C and N should be managed in conjunction with one another in order to improve N use efficiency and N retention (Drinkwater and Snapp 2007;Fisk et al 2015).…”
Section: Ecologically-based Nutrient Management Practicessupporting
confidence: 54%
See 2 more Smart Citations
“…Previous field and laboratory studies have reported such relationships under similar environmental conditions (Huang et al 2004;Gomes et al 2009). The fact that this relationship emerged despite environmental variation further highlights the importance of C abundance in regulating N 2 O emissions and supports the idea that C and N should be managed in conjunction with one another in order to improve N use efficiency and N retention (Drinkwater and Snapp 2007;Fisk et al 2015).…”
Section: Ecologically-based Nutrient Management Practicessupporting
confidence: 54%
“…The N saturation conceptual model highlights the significance of C-N coupling in driving N retention/loss and has led to major advances in C and N, and more recently, P biogeochemistry (Fenn et al 1998;Luo et al 2004;Magnani et al 2007;De Schrijver et al 2008;Mulholland et al 2008;Schlesinger 2009;Fenn et al 2010;Vitousek et al 2010;Crowley et al 2012). Application of this conceptual framework could have similar ramifications for N management in agricultural systems (Drinkwater and Snapp 2007;Thorburn et al 2011;Fisk et al 2015;Attard et al 2016;Tosti et al 2016).…”
Section: Nitrogen Saturation Theory and Agroecosystemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the paddy and forest soil, the denitrification was unapparent under neutral aerobic (Lan et al, 2015;Pajares and Bohannan, 2016) and/or nitrogen deficiency conditions (Pajares and Bohannan, 2016). In addition, root exudate carbon was previously observed to be effective at decreasing the risk of N loss by increasing the potential for heterotrophic microbial immobilization (Fisk et al, 2015) and plant roots might not provide an appropriate survival environment for denitrifiers (Fisk et al, 2015). Under aerobic conditions, the nitrogen loss was mainly attributable to ammonia oxidizers (Florio et al, 2016), and in this study the stimulating effects of plant roots on ammonia oxidizers still did not aid the accumulation of nitrogen.…”
Section: Discussionmentioning
confidence: 99%
“…This was the first report of new land use pattern by co-cropping herbal plant to mitigate N 2 O emitted from agricultural soil. Compared to some other agricultural practices such as N fertilizer management (KAISER et al, 1998;Ulrike et al, 2003;Chu et al, 2007;Fub et al, 2011;Aguilera et al, 2013;Fisk et al, 2015;Frederico et al, 2015), reduced tillage (Fub et al, 2011;Fisk et al, 2015;Frederico et al, 2015), drip irrigation and fertigation (Aguilera et al, 2013;Kennedy et al, 2013), organic amendments (Qiu et al, 2013;Aguilera et al, 2013;Fisk et al, 2015), crops straw incorporation (Ma et al, 2009;Yang et al, 2015), biochar (Xiang et al, 2015), nitrification inhibitor (Ranucci et al, 2011;Barneze et al, 2015), this newly developed approach could be more effective and economical as it was simple and easily to conduct in a low-cost manner for farmer. Of course, it needs to be further improved and optimized.…”
Section: Discussionmentioning
confidence: 99%